2018
DOI: 10.1113/ep087038
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of heat shock proteins and activation of mitogen‐activated protein kinases in A549 alveolar epithelial cells exposed to cigarette smoke extract

Abstract: New Findings What is the central question of this study?What is the effect of cigarette smoke on cell death, oxidative damage, expression of heat shock proteins (HSPs) and activation of mitogen‐activated protein kinases (MAPKs) in A549 alveolar epithelial cells? What is the main finding and its importance?Cigarette smoke induces cytotoxicity and oxidative damage to A549 cells, increases expression of different HSPs and activates MAPK signalling pathways. This could be related to inflammatory response and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…However, when cells are damaged beyond repair, the UPR promotes elimination of afflicted cells through apoptosis [61]. Previous studies have also reported an increase in the expression of heat shock proteins in the alveolar epithelial cells exposed to cigarette smoke extract [62]. TCTP, a pro-survival molecule, has also been shown to play an important role in the UPR where it protects cells from the apoptotic cell death [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when cells are damaged beyond repair, the UPR promotes elimination of afflicted cells through apoptosis [61]. Previous studies have also reported an increase in the expression of heat shock proteins in the alveolar epithelial cells exposed to cigarette smoke extract [62]. TCTP, a pro-survival molecule, has also been shown to play an important role in the UPR where it protects cells from the apoptotic cell death [61].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of heat shock proteins is increased in the alveolar epithelial cells exposed to cigarette smoke extract [62] (P08238)…”
Section: B2mmentioning
confidence: 99%
“…Nevertheless, there were probably hundreds of miRNAs that are upregulated or downregulated in COPD (Ezzie et al, 2012;Osei et al, 2015;Sato et al, 2015;Szymczak et al, 2016;Conickx et al, 2017;Keller et al, 2018), and the aim of the present study was only to examine those that could modulate the CCL3/CCR5 axis. In addition, although A549 cells were used to study alveolar epithelial cells (Akram et al, 2013;Mortaz et al, 2017;Somborac-Bacura et al, 2018), they were malignant cells that might not reflect reality. Future studies should be done to examine a wide panel of miRNAs, and also to deline at the effects of circulating miRNAs vs. those of miRNAs produced locally in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…After 6 hr, the expression of HSP70 and HSP32 will be increased by CSE induce. And fortunately, all detected HSPs are upregulated after 8 hr and continuously increased to 48 hr (Somborac‐Bačura et al., 2018). Smoke and some other polluting gases were easily breathed in goats during the transport period.…”
Section: Discussionmentioning
confidence: 99%